2013
DOI: 10.1051/epjconf/20135001004
|View full text |Cite
|
Sign up to set email alerts
|

Radiotracer investigations to study the hydrodynamic characteristics of continuous phase in a pulsed sieve plate extraction column

Abstract: Abstract. The present investigations are focused to study the hydrodynamic characteristics of continuous phase in a pulsed sieve plate extraction column using 68 Ga in the form of gallium chloride from an industrial radionuclide generator ( 68 Ge/ 68 Ga). Labeling of water with the subject radiotracer in water-kerosene environment was evaluated. Experiments for Residence Time Distribution (RTD) analysis were carried out for a range of dispersed phase superficial velocities in a liquid-liquid extraction pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This technology has been extensively employed to help unravel industrial hitches in advanced economies, but it is still underutilized in Global South nations due to the lack of radiotracers at the point of need. It is required to import radiotracers for Global South countries that do not have radioisotope manufacturing facilities, and the long amount of time needed in this process eliminates the prospect of realizing the prospective benefits of this technology [99]. The gap can be partially addressed by building or installing affordable neutron generators or sources and research reactors in these countries through local and international support.…”
Section: The Radiotracer Methodsmentioning
confidence: 99%
“…This technology has been extensively employed to help unravel industrial hitches in advanced economies, but it is still underutilized in Global South nations due to the lack of radiotracers at the point of need. It is required to import radiotracers for Global South countries that do not have radioisotope manufacturing facilities, and the long amount of time needed in this process eliminates the prospect of realizing the prospective benefits of this technology [99]. The gap can be partially addressed by building or installing affordable neutron generators or sources and research reactors in these countries through local and international support.…”
Section: The Radiotracer Methodsmentioning
confidence: 99%
“…The liquid in a PSPC passes through the sieve perforations, whereas the liquid in a PDDC follows a tortuous flow path. Each of these columns has its own advantages and disadvantages. , Several studies have reported the pressure drop, axial dispersion, drop size distribution, and dispersed phase hold-up in the PSPC and PDDC. The PDDC is employed for uranium recovery and purification at the front end, while the PSPC is employed for the back-end processes of the nuclear fuel cycle. Both columns play crucial roles in nuclear industry applications and have been studied extensively by researchers for their respective purposes. , …”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al proposed an empirical correlation to predict the overall mass transfer coefficient, which was in good agreement with the experimental values. Din et al used a radioisotope-based technique to study residence time distribution (RTD) and developed a dispersion model. They have mentioned axial mixing and holdup of the dispersed phase in a PSPC increased with an increase in pulsation frequency and amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al 3 proposed an empirical correlation to predict the overall mass transfer coefficient, which was in good agreement with the experimental values. Din et al 17 Goswami et al 18 reported a single-phase RTD study in PSPC using a technetium (Tc-99m)-based radiotracer. Yadav et al 13 reviewed various published data on hydrodynamics and mass transfer performance of PSPC and commented on the suitability of different correlations to predict different dependent variables like mass transfer coefficient, holdup, and drop diameter.…”
Section: Introductionmentioning
confidence: 99%